Nutrient content and physical characteristics linkage of palm kernel meal and coconut meal after wet separation using molecular weight approac - AINUN NAFISAH (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2022)
The use of palm kernel meal and coconut meal is restriction in broiler feed due to the high crude fiber content, caused by the mixture of shells. This study aims to analyze the nutrient content, i.e., crude protein and crude fiber of palm kernel meal and coconut meal before and after using wet separation and molecular weight approach. The wet separation process for palm kernel meal and coconut meal was carried out for 6 hours to obtain a precipitate. The palm kernel meal and coconut meal that have been separated is divided into 3 fractions, i.e., upper, middle and lower. Each fraction was analyzed for crude fiber and crude protein content for chemical characteristics, and bulk density (g l-1), compacted bulk density (g l-1), specific gravity (kg l-1), angle of purpose (o). Crude protein and crude fiber content of palm kernel meal before being separated by wet separation were 11.72% and 13.11%, for coconut meal were 12.65% and 8.67%. The fraction of palm kernel meal has the highest crude protein content of 22.21% with the lowest crude fiber content 9.68%. Coconut meal in the middle fraction had the highest crude protein content 18.92% and the lowest crude fiber content of 11.95% in the upper fraction. The physical characteristics of the upper fraction of palm kernel meal and coconut meal had the lowest values (P0.05) of specific gravity (kg l-1), bulk density (g l-1) and compacted bulk density (g l-1). It can be concluded that the wet separation process with the molecular weight approach is able to increase the nutrient content especially of each fraction and can minimize the mixture of shells in palm kernel meal and coconut meal